PENETAPAN UKURAN SASARAN SEBAGAl SUATU CARA PENGENDALIAN KUALITAS DI KILANG PENGGERGAJIAN - Sutarso Priasukmana; Sylviani Sylviani; Unang Suratman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1986)
A study of quality control application on sawn-timber was conducted on several sawmills in Sumatra, West Kalimantan and East Kalimantan. Sample sawmills are selected based on market orientation and the availability of drying facibilities.The objectives of this study are to introduce new methode of quality control for sawn timber, in this target sise determination, and to evaluate the quality control practices in exitng' sawmill operationt.The results of the study show that all the sampled sawmills did not have a apecific program of quality control, nor special personnels responsible for quality control.Green board thicness set by surveyed sawmills were higher than what is actually reguired, ranging between 1 to 23 percent above the calculated target size. This is an indication that there is a lot of room improving the efficiency of raw material usqge through the application of target size settling formula.